1990
DOI: 10.1007/bf00192462
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection during childhood: detection of viral DNA in peripheral blood by means of polymerase chain reaction

Abstract: Polymerase chain reaction (PCR) technique was applied to detect cytomegalovirus (CMV) DNA. Two pairs of synthetic oligonucleotide primers were used to amplify DNA from the immediate early 1 and the late antigen genes of CMV, respectively. Either primer sets could detect as few as 0.01 plaque-forming unit of CMV strain AD 169 by Southern blot hybridization. Sixteen CMV clinical isolates were examined and all were found to be positive by the both primer sets. The PCR was used to detect CMV DNA in peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…195, 4 ml of 5 mM each dNTPs, 4 ml of 5x reverse transcriptase sackie viruses and Echovirus), with the exception of echovirus 22 and 23 (46). A second primer pair, buffer (51 buffer Å 15 mM MgC12, 50 mM dithiothreitol, 250 mM Tris, pH 8.3, and 375 mM KCl), 200 units designed to amplify a 607-bp product was created from the immediate early gene of the AD169 strain of Maloney murine leukemia virus (MoMLV) reverse transcriptase (BRL-Gibco), and DEPC-treated dH 2 O to of CMV, recognizing all CMV serotypes (33). The third primer pair was designed to amplify a 308-20 ml; this reaction was incubated at 37ЊC for 1 h. Two microliters of this first-strand cDNA or 500 ng of control bp sequence of the hexon region of all adenovirus serotypes (except adenovirus 40,41) (29).…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…195, 4 ml of 5 mM each dNTPs, 4 ml of 5x reverse transcriptase sackie viruses and Echovirus), with the exception of echovirus 22 and 23 (46). A second primer pair, buffer (51 buffer Å 15 mM MgC12, 50 mM dithiothreitol, 250 mM Tris, pH 8.3, and 375 mM KCl), 200 units designed to amplify a 607-bp product was created from the immediate early gene of the AD169 strain of Maloney murine leukemia virus (MoMLV) reverse transcriptase (BRL-Gibco), and DEPC-treated dH 2 O to of CMV, recognizing all CMV serotypes (33). The third primer pair was designed to amplify a 308-20 ml; this reaction was incubated at 37ЊC for 1 h. Two microliters of this first-strand cDNA or 500 ng of control bp sequence of the hexon region of all adenovirus serotypes (except adenovirus 40,41) (29).…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…nucleic acid extraction. PCR and RT-PCR were per-Control Samples formed as described previously (15,29,30,33,42,43,47,49,50). Amniotic fluid samples were collected for genetic…”
mentioning
confidence: 99%
“…In some studies, HCMV DNA has been detected in the peripheral blood mononuclear cells of healthy blood donors,' 5*28 but other studies have found HCMV DNA only in leukocytes from severely immunosuppressed patients. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In our study, HCMV DNA was detected by amplification in the peripheral blood mononuclear cells of normal healthy individuals who were negative for urinary excretion (data not shown). This is why we used urinary excretion as the method for monitoring HCMV infection.…”
Section: Discussionmentioning
confidence: 84%
“…The second group consisted of 20 children with acute or chronic hepatitis of unknown etiology (mean age 2.9 years). Hepatitis A, B, C, and GB virus type C, and infantile hepatitis with herpesviruses (cytomegalovirus or Epstein-Barr virus) were ruled out in these patients [12,22,23,32]. The third group included 18 children who were transfusion recipients or hemophiliacs (mean age 8.2 years).…”
Section: Study Populationmentioning
confidence: 99%